2005
DOI: 10.1093/brain/awh683
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology of fragile X-associated tremor/ataxia syndrome (FXTAS)

Abstract: Fragile X-associated tremor/ataxia syndrome (FXTAS) is an adult-onset neurodegenerative disorder that affects carriers, principally males, of premutation alleles (55-200 CGG repeats) of the fragile X mental retardation 1 (FMR1) gene. Clinical features of FXTAS include progressive intention tremor and gait ataxia, accompanied by characteristic white matter abnormalities on MRI. The neuropathological hallmark of FXTAS is an intranuclear inclusion, present in both neurons and astrocytes throughout the CNS. Prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

62
589
7
15

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 492 publications
(673 citation statements)
references
References 35 publications
62
589
7
15
Order By: Relevance
“…Six cases (cases 1,7,9,11,12,14) were diagnosed with mood disorders, while 4 cases (cases 4, 7, 9, 11) were diagnosed with anxiety disorders. Table 2 details demographic data, number of CGG repeats, years of FXTAS, age of FXTAS onset, FXTAS stage, psychiatric diagnoses, degree of MCP sign, and other MRI findings, as well as a description of FXTAS stages.…”
Section: Resultsmentioning
confidence: 99%
“…Six cases (cases 1,7,9,11,12,14) were diagnosed with mood disorders, while 4 cases (cases 4, 7, 9, 11) were diagnosed with anxiety disorders. Table 2 details demographic data, number of CGG repeats, years of FXTAS, age of FXTAS onset, FXTAS stage, psychiatric diagnoses, degree of MCP sign, and other MRI findings, as well as a description of FXTAS stages.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of the knock-in mouse model of the premutation (Entezam et al 2007), FMRP expression was significantly reduced in several brain regions, including the hippocampus. In those brain areas sampled in post mortem studies of brain tissue from older premutation males with FXTAS, the hippocampus shows the largest percentage of cells with intranuclear inclusions, again suggesting that this brain region may be particularly affected in FXTAS (Greco et al 2002(Greco et al , 2006. Our current working hypothesis for psychiatric and cognitive involvement among carriers of premutation alleles posits that clinical features arise through a combination of RNA toxicity and mild reductions of FMRP.…”
Section: Introductionmentioning
confidence: 89%
“…Kenneson et al (2001) [10] found that these patients have an increase in FMR1 RNA transcription proportionally related to the number of CGG repeats and a decrease in FMRP translation inversely related to the number of CGG repeats. The excess of FMR1 mRNA seen in carriers leads to dysregulation of several proteins and its deposition, along with FMR1 mRNA, in the form of cellular inclusions in several parts of the body including the central nervous system, peripheral nervous system (especially autonomic ganglia), Leydig cells, and pituitary among others [11][12][13]. Therefore, any pathology associated with FMR1 premutations would not be caused by a complete absence of FMRP like FXS is, but probably due to partial FMRP deficiency and/or RNA toxicity.…”
Section: Introductionmentioning
confidence: 99%